Fear vs. Joy of Missing Out in the Digital Context: The Interplay between Psychological Constructs and Constant Checking - Yilmaz, Feride (My University, 2026)
Fear and joy of missing out (FOMO/JOMO) represent two psychological constructs that can shape individuals’ checking behavior in daily life. Despite being seemingly opposites, both provide valuable insights into the emotional and behavioral dynamics of IT usage in today’s world of constant connectivity. However, FOMO and JOMO have mainly been examined quantitatively, and to date there has been no study that addresses both concepts in relation to constant checking behavior. Therefore, this thesis explores qualitatively how 11 individuals between the ages of 22 and 33 experience FOMO and JOMO in relation to their constant checking behavior, based on semi-structured interviews. The findings emphasize the situational and contextual aspects of FOMO and JOMO. It emerges that JOMO differs significantly from mere functional regulation methods in terms of motivation and associated emotions. In addition, individuals are often aware of their distorted FOMO and increased checking, but find it challenging to change these patterns in a lasting way. The thesis also outlines potential approaches for creating JOMO experiences and reducing the frequency of checking.
Keywords: FOMO; JOMO; constant checking; IT-mediated state-tracking